The effect of virtual cognitive-behavioral sexual counseling on sexual function and sexual intimacy in pregnant women: a randomized controlled clinical trial - Manizheh Fathalian; Razieh Lotfi; Mahbobeh Faramarzi; Mostafa Qorbani (BMC, 2022)
Abstract Background & aim Pregnancy is associated with numerous physical and psychological changes and affects the sexual function of couples. Since the root of many marital problems lies in the quality of the relationship and sexual function, the present study investigates the effect of virtual cognitive-behavioral sexual counseling on pregnant women's sexual function and intimacy. Methods & Materials This study is a randomized clinical trial, and 80 pregnant women aged 18 to 35 years and in 16-24 weeks of pregnancy were assigned to two intervention and control groups based on randomized blocks from June 2021 to July 2021. The control group received routine prenatal care, but the intervention group, in addition to routine prenatal care, underwent virtual counseling with a cognitive-behavioral approach during eight sessions of 90 minutes. Data were collected using the Female Sexual Function Index (FSFI) and sexual intimacy questionnaire. SPSS software was used for statistical analysis. Results The comparison of mean scores of sexual function and intimacy in the two groups before the intervention was not statistically significant with each other. However, after the intervention, the mean scores of sexual function and intimacy in the intervention group were significantly increased compared to the control group (p < 0.001). The effect size of the intervention was 0.52 for sexual function and 0.272 for sexual intimacy. Conclusion Virtual cognitive-behavioral counseling can be used as an effective treatment to promote sexual function and intimacy of women during pregnancy. Trial registration IRCT20161230031662N10. Registry date: 21/06/2021.